Accuracy of the clinical indicators of ineffective health management in celiac people - Leonardo Alexandrino da Silva; Cristina Costa Bessa; Nirla Gomes Guedes; Marcos Venícios de Oliveira Lopes; Viviane Martins da Silva; Jorgiana Cavalcanti dos Santos; Patricia Fernandes Chaves (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze the accuracy of clinical indicators of "Ineffective health management" in celiac patients and to verify associations between sociodemographic characteristics and clinical indicators. Method: a cross-sectional study, conducted from May to September 2017, with 83 celiac patients, through an interview. Accuracy measures were defined by latent class model. Results: there was a prevalence of "Ineffective health management" of 55.69%. "Failure to take action to reduce risk factor" and "Failure to include treatment regimen in daily living" better predict this diagnosis. Paid occupation reduces the chance of the presence of "Difficulty with prescribed regimen". Participation in support association reduces the chance of the presence of "Difficulty with prescribed regimen", "Ineffective choices in daily living for meeting health goal" and "Failure to take action to reduce risk factor". Conclusion: accurate clinical indicators identification assists clinical reasoning for diagnostic inference in specific health contexts.